The role of bond strength in structural behaviors of UHPC-NC composite beams: Experimental investigation and finite element modeling. (1st January 2021) - Tong, Teng; Yuan, Siqi; Wang, Jingquan; Liu, Zhao
Highlights: Four-point loading tests were performed on composite beams with varying thickness of the UHPC layer. Specimens for slant shear test were improved to obtain the bond strength in a realistic manner. A novel cohesive-friction model is proposed for the UHPC-NC interface. The FE simulations are performed with user subroutines being supplied. Abstract: The booming application of UHPC-NC composite members renders the interfacial behavior a critical role in their macro-scale structural behaviors. Four composite beams were monotonically loaded to failure, with various thickness of the UHPC layer. The occurrence of UHPC-NC interface debonding demonstrated the role of bond strength. To this end, the standard slant shear test was improved and performed to quantify the bond strength in a realistic manner. For the computational aspects, reliable finite element (FE) models are constructed, which adopt the localizing gradient-enhanced model for the bulk region (UHPC and NC), the Menegotto-Pinto model for rebars, and a coupled cohesive-friction model for the interface. The meso-mechanical assumption is employed to smoothly integrate the cohesion with the friction. Viscous regularization is adopted to suppress the instability and the convergence problem. Identification of model parameters is well performed and presented. These FE models are verified with the tested composite beams, which offer a valuable insight to the evolution and distribution of normal and tangential tractions along the UHPC-NC interface. It is demonstrated that all the analyses are realized with the implicit incremental-iterative algorithm.